Design and Analysis of Frequency Selective Surface (FSS) Using Complementary Techniques on Glass - Hussin, F.A.; Ahmad, B.H.; Aziz, M.Z.A.A.; Suaidi, M.K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the design of square Frequency Selective Surface (FSS) based on a complementary technique for energy saving glass (ESG) application. In this paper, there are four designs of FSS that have been presented which are a square patch (Design A), square patch rectangular slot (Design B), complementary square patch with a rectangular slot (Design C) and complementary square patch with rectangular slot and square loop (Design D). All design used glass as a substrate and aluminum as the conductive patches. The unit cells of each design are simulated using CST Microwave Studio software. The simulation process is based on the characteristics of reflection coefficient (S11) and transmission coefficient (S21) of the FSS. The simulation result shows that Design B exhibit pass band at 5.2 GHz. While, Design D produce dual pass band at 1.7 GHz and 5.2 GHz. Therefore, this design can be used to improve the transmission of the wireless communication signal.